THE EFFECT OF COMPANY SIZE, PROFITABILITY, AND SOLVENCY ON AUDIT DELAY IN COMPANIES - Sri Wahyuni; Netty Herawaty; Achmad Hizazi (Yayasan Nuraini Ibrahim Mandiri, 2026)
This study aims to analyze the effect of firm size, profitability, and solvency on audit delay using the Systematic Literature Review (SLR) method. The study employed 15 articles published during the 2021–2026 period obtained from Google Scholar. The results indicate that most studies found that firm size and profitability tend to reduce audit delay, while solvency tends to prolong audit delay. A total of 10 articles supported the effect of firm size on audit delay, 8 articles supported the effect of profitability, and 9 articles supported the effect of solvency. Meanwhile, several other studies reported insignificant results due to differences in industry characteristics, operational complexity, and the quality of the company’s internal control systems. This study demonstrates that audit delay is influenced not only by the company’s financial condition but also by the effectiveness of corporate governance and the company’s audit process.